Structural GARCH: The Volatility-Leverage Connection - Engle, Robert F.; Siriwardane, Emil N. (Review of Financial Studies, 2018)
In the aftermath of the financial crisis, institutions have been asked to reduce leverage in order to reduce risk. To address the effectiveness of this measure, we build a model of equity volatility that accounts for leverage. Our approach blends Merton’s insights on capital structure with traditional time-series models of volatility. We estimate that precautionary capital needs for the entire financial sector reached $2 trillion during the crisis. We also investigate the long-standing observation that equity volatility asymmetrically responds to positive and negative news. Volatility asymmetry is mostly explained by exposure to the aggregate market, not a mechanical leverage effect. Received March 27, 2015; editorial decision February 25, 2017 by Editor Andrew Karolyi.